Hybridization among Brazilian oat (Avena sativa L.) cultivars and the wild oat A. sterilis L. - Sereno-Tavares, Maria Jane C. M.; Bodanese-Zanettini, Marla Helena; de Carvalho, Fernando I. F. (Pesquisa Agropecuaria Brasileira, 1995)
Hybrids among Avena sativa (L.) Brazilian cultivars and A. sterilis L. accessions were obtained without in vitro embryo culture. Parental samples and their hybrids were investigated by morphological characters of spikelets, meiotic chromosome behaviour and esterase isoenzymes analysis. The F<span style="line-height: 115%; font-family: ";Calibri";,";sans-serif";; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: PT-BR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">1 hybrids were intermediate to the parental lines for the morphological spikelet characters. The high esterase zymotype affinity made difficult the diagnostic of the hybrid condition. The hybrids presented more meiotic irregularities than the parental lines. However, predominant bivalent formation shows that the corresponding chromosomes in A. sativa and A. sterilis are able to pair effectively and should result in the recombination of characters of the two species.